Chitosan Nanoparticles : A Promising System for Drug Delivery - Tiyaboonchai, Waree (Asian Health, Science and Technology Reports, 2003)
Chitosan nanoparticles have gained more attention as drug delivery carriers because of their better stability, low toxicity, simple and mild preparation method, and providing versatile routes of administration. Their sub-micron size not only suitable for parenteral application, but also applicable for mucosal routes of administration, i.e., oral, nasal, and ocular mucosa, which are non-invasive route. The application for mucosal delivery also facilitated by chitosan absorption enhancing effect. Furthermore, chitosan nanoparticles also showed to be a good adjuvant for vaccines. Therefore, the objectives of this review are to summarize the available preparation techniques involved chitosan nanoparticles, the application of explored chitosan nanoparticles, and the mechanism of cell entry.